(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
In order to better understand the mediating and moderating impacts of talent matching, this study examines the relationship between quality hiring and the implementation of HR 4.0 technology. The theories suggest that the implementation of HR 4.0 technology has a substantial direct impact on quality hires as well as an indirect impact through talent matching acting as a moderating and mediating element. This study investigates the substantial influence that HR 4.0 technologies have on firms’ ability to hire top talent. Through a careful analysis of the literature and empirical data, this study clarifies the complicated implications of cutting-edge technological tools like automation, machine learning, artificial intelligence (AI), and data analytics on the recruiting and selection process. These results demonstrate how crucial it is to apply successful talent matching techniques in addition to HR 4.0 technologies to improve the quality of hires made by firms. Future research directions are suggested, along with implications for theory and practice.